THE APPLICATION OF PAPERLESS AND GREEN THEORY IN NATIONAL DEFENCE UNIVERSITY OF MALAYSIA: A CONCEPTUAL STUDY - Hasan Al-Banna Mohamed; Mohd Hamran Mohamad; Sayuti Ab Ghani; Rogis Baker; Kamarulzaman Lamin; Norlaila Mazura Mohaiyadin; Khairunnisa Mardzuki (The Republic of Indonesia Defense University, 2020)
The green environment through electronic government is seen increasingly more useful in today’s economy and business due to its effectiveness and applicability in various fields. Paperless is the reduction of paper usage practiced by the employees in many workplaces which is an important element in national electronic government today. Despite the rapid acculturation of paperless systems in many organizations, researchers have argued that it is yet to promote and establish a paperless practice that leads to sustainable and reliable approaches especially in the working environment at the National Defense University of Malaysia (NDUM) due to high perceived profitability by the stakeholders. Evidence shows that the traditional use of the paper-based process in daily working practices leads to many weaknesses, risks, and financial burdens. This implies that it will be very important to truly embed behavioral intention (desire towards paperless practice) within a community of NDUM if individual perceptions of the use of information technology (IT) in the e-government service is the motivator factor. The paper aims to propose a study on the relationship of perceived organizational support dimensions (IT, management and peer supports) within the paperless context which is grounded by a famous theory namely Technology Acceptance Model (TAM). A literature study is used as a method to yield related findings. Thus, this paper provides a research model (conceptual) to extend the knowledge of how organizational support influences employees’ behavioral intention in practicing paperless. This study is then constructed into possible research hypotheses for future empirical researches. The model of research will provide a beneficial guideline for strategies determination in promoting e-government services, particularly the paperless based service.